Profile of Extrovert and Introvert Personality and The Implications in Problem Based History Learning - Megiridha Loppies; Aip Badrujaman; Sarkadi Sarkadi (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
This research is motivated by differences in personality types that caused by differences in thinking abilities which also have an impact on student learning outcomes. The purposes of this study was to identify and analyze the personality types of students and their implications for learning history at SMAS Pusaka 1 Jakarta. The personality types that used in this study are extrovert and introvert personality types according to Carl Gustaf Jung (Arip et al., 2017). The subjects in this study were students of class XI IPS at SMAS Pusaka 1 Jakarta for the 2020/2021 school year. The method used in this research is descriptive qualitative using a questionnaire to collect data on student personality types and then analyzed descriptively. The results showed that extrovert students were more able to build work communication in groups so that they could find more information related to the problems given. However, the information managed by extrovert students is still superficial and less logical. Meanwhile, introverted students are able to use information in answering the problems given by in-depth analysis. The implication of this research is teachers must be able to better understand the personality types of students, both extrovert and introvert to generate more effective learning.